Concerted proton-electron transfer oxidation of phenols and hydrocarbons by a high-valent nickel complex. Issue 6 (13th January 2020) - Fisher, Katherine J.; Feuer, Margalit L.; Lant, Hannah M. C.; Mercado, Brandon Q.; Crabtree, Robert H.; Brudvig, Gary W.
Abstract : A high-valent nickel(III) compound performs fast concerted proton–electron transfer on O–H and C–H bonds. Thermodynamic analysis suggests that the oxidizing power of the compound and the formation of a strong ligand O–H bond lead to high reactivity. Abstract : The high-valent nickel(iii ) complex Ni(pyalk)2 + (2 ) was prepared by oxidation of a nickel(ii ) complex, Ni(pyalk)2 (1 ) (pyalk = 2-pyridyl-2-propanoate). 2 and derivatives were fully characterized by mass spectrometry and X-ray crystallography. Electron paramagnetic resonance spectroscopy and X-ray photoelectron spectroscopy confirm that the oxidation is metal-centered. 2 was found to react with a variety of phenolic and hydrocarbon substrates. A linear correlation between the measured rate constant and the substrate bond dissociation enthalpy (BDE) was found for both phenolic and hydrocarbon substrates. Large H/D kinetic isotope effects were also observed for both sets of substrates. These results suggest that 2 reacts through concerted proton-electron transfer (CPET). Analysis of measured thermodynamic parameters allows us to calculate a bond dissociation free energy (BDFE) of ∼91 kcal mol −1 for the O–H bond of the bound pyalk ligand. These findings may shed light onto CPET steps in oxidative catalysis and have implications for ligand design in catalytic systems.